Angioarchitectural Characteristics Associated with Complications of Embolization in Supratentorial Brain Arteriovenous Malformation - Pan, J. (AJNR Am J Neuroradiol, 2014)
BACKGROUND AND PURPOSE: Embolization is an important therapeutic technique in brain arteriovenous malformations; however, little has been reported on the factors contributing to complications. We retrospectively reviewed a large series of supratentorial brain AVMs to identify the angioarchitectural characteristics that might be associated with the complications of embolization and poor clinical outcomes. MATERIALS AND METHODS: The clinical and angiographic features of 130 consecutive patients with supratentorial brain AVMs embolized with ethylene-vinyl alcohol copolymer in our hospital from 2005–2008 were retrospectively reviewed. None of these patients had prior embolization. Complications were classified as transient neurologic deficits, persistent neurologic deficits, and death. Univariate and multivariate analyses were conducted to assess the angiographic features in patients with and without complications. RESULTS: Twenty-three complications occurred in 130 embolization procedures, 13 (10%) were transient neurologic deficits (9 ischemic and 4 hemorrhagic), 9 (6.92%) were persistent neurologic deficits (7 ischemic and 2 hemorrhagic), and 1 death occurred. By univariate analyses, eloquent cortex (OR, 2.57; 95% CI, 1.08–3.42) and exclusive deep venous drainage (OR, 4.56; 95% CI, 1.28–9.67) were correlated with procedural complications. The impaction of eloquent cortical location (P = .001) and exclusive deep venous drainage (P = .035) on complications were also demonstrated by multivariate analysis. Eloquent cortex mainly resulted in permanent ischemic neurologic deficit; occlusion of drainage vein was significantly correlated with periprocedural hemorrhage in supratentorial brain AVMs with subtotal and partial embolization. CONCLUSIONS: In a retrospective study on supratentorial brain AVMs with first-time embolization, 6.92% of patients had permanent neurologic deficit or death. Eloquent cortical location and exclusive deep venous drainage were associated with complications.